ANALISIS PERMASALAHAN PEMBELAJARAN IPAS KELAS IV SDN 182/I HUTAN LINDUNG - Firdia Tri Agustin; Halimatus Sa'diah; Nabila Salsabila; Abraar Dzulqadri (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research aims to analyze the problems of class IV science learning at SDN 182/I Hutan Lindung. The research method used in this research is a qualitative approach. The data sources in this research are the class IV homeroom teacher at SDN 182/I Hutan Lindung and class IV students at SDN 182/I Hutan Lindung. Data collection techniques in this research used observation, interviews and document study techniques. The data analysis technique in this research uses the Miles and Huberman model, namely data collection, data reduction, data presentation, as well as drawing conclusions and verification. The research procedure is carried out in three stages, namely the preparation stage, the implementation stage, and the completion and report preparation stage. The results of the research show that in class IV of SD Negeri 182/I Hutan Lindung there are several learning problems. Through this research, it is hoped that it can become a benchmark for educators so that they can improve learning in the future, so that learning can be carried out better.